Lipase production: An insight in the utilization of renewable agricultural residues - Salihu, Aliyu; Alam, Md Zahangir; AbdulKarim, M. Ismail; Salleh, Hamzah M. (Elsevier, 2012)
Bioconversion of agricultural residues for lipase production as well as other value added products would hold a prominent position in future biotechnologies, mainly because of its eco friendliness and flexibility to both developing and developed countries. Several residues such as straw, bran, oil cakes, among others attract increasing attention as abundant and cheap renewable feedstock. Many researchers considered improvement of substrate composition, physical parameters (temperature, pH, moisture content and particle size), inoculum concentration, and substrate porosity to upgrade and valorize these bioproducts. Several species of fungi, yeast and bacteria have been used in utilizing the agricultural residues through fermentation techniques due to their ability to grow on particle surfaces as sources of carbon and energy, and produce important industrial enzymes including lipases. This review provides an overview of the present status on the utilization of renewable residues in the form of solid- and liquid-state and their characteristics for production of lipases using different microbial systems.